Algebraic invariants of the edge ideals of whisker graphs of cubic circulant graphs - Mujahid Ullah Khan Afridi; Ibad Ur Rehman; Muhammad Ishaq (Heliyon)
Let Q be a polynomial ring over a field F and I be an edge ideal associated with the whisker graph of a cubic circulant graph. We discuss the regularity, depth, Stanley depth, and projective dimension of Q/I.